1987
DOI: 10.1097/00006254-198707000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Blood Group Antibody Screening Tests during Pregnancy

Abstract: In a 2-year period 667 sera from approximately 70000 (0.95%) antenatal patients were found to contain 726 atypical red blood cell antibodies. Overall, 66% of the immunized mothers were rhesus (D) positive. Apart from four antibody specificities to rhesus system antigens, knowledge of the rhesus (D) group gave no guide to the ability of the patients to form any of the remaining 21 specificities encountered. Of the 726 antibodies 221 (30%) were not detected in the initial sample tested and 50 of the 92 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 4 publications
(5 reference statements)
3
27
0
Order By: Relevance
“…In the Western population, alloimmunization against red cell blood group antigens occurs in about 1% of pregnancies (Bowell et al, 1986). Anti-D, anti-Kell and anti-c are the antibodies most often implicated in the causation of moderate to severe HDN and account for about 40% of the antibodies detected in pregnant women (Bowell et al, 1986).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Western population, alloimmunization against red cell blood group antigens occurs in about 1% of pregnancies (Bowell et al, 1986). Anti-D, anti-Kell and anti-c are the antibodies most often implicated in the causation of moderate to severe HDN and account for about 40% of the antibodies detected in pregnant women (Bowell et al, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…Anti-D, anti-Kell and anti-c are the antibodies most often implicated in the causation of moderate to severe HDN and account for about 40% of the antibodies detected in pregnant women (Bowell et al, 1986). Although Rh D typing and anti-D prophylaxis have resulted in a reduction of fetal loss and neonatal death due to HDN, alloimmunization due to other antigens such as Kell and c continues to be important (MacKenzie et al, 1992 Abbreviations: G, gravida; P, parity; NSD, normal spontaneous delivery; Hb, haemoglobin; DAT, direct antiglobulin test; rbc, red blood cell; HDN, haemolytic disease of the newborn; SLL, small lymphocytic lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…In the province of Tirol Schönitzer [5] discovered a prevalence of relevant antibodies of 0.58% between 1971 and 1985. For the region of Oxford Bowell et al [6] described a prevalence of antibodies among pregnant women of 0.98% between 1984 and 1985. This variability of the prevalence might be caused by regional differences; on the other hand, the higher prevalence in Salzburg might also be due to the higher sensitivity of the ABST since the introduction of gel centrifugation techniques.…”
Section: Discussionmentioning
confidence: 99%
“…RhD(-) women are then retested during the second and third trimes ters, in contrast to RhD(+) women. In a survey of pregnant women, Bowell et al [13] have shown that 66% of those producing antibodies during pregnancy were RhD(+). In our present study, after excluding the RhIG, 71% of those producing antibodies were RhD(+).…”
Section: The Sph Screening Testmentioning
confidence: 99%